2009
DOI: 10.1007/s00410-009-0465-7
|View full text |Cite
|
Sign up to set email alerts
|

Stability and chemical equilibrium of amphibole in calc-alkaline magmas: an overview, new thermobarometric formulations and application to subduction-related volcanoes

Abstract: This work focuses on a rigorous analysis of the\ud physical–chemical, compositional and textural relationships\ud of amphibole stability and the development of new\ud thermobarometric formulations for amphibole-bearing calcalkaline\ud products of subduction-related systems. Literature\ud experimental results (550–1,120C, \1,200 MPa, -1 B\ud DNNO B ?5), H2O–CO2 solubility models, a multitude of\ud amphibole-bearing calc-alkaline products (whole-rocks and\ud glasses, representing 38 volcanoes worldwide), crustal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

48
822
2
36

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 1,012 publications
(908 citation statements)
references
References 129 publications
48
822
2
36
Order By: Relevance
“…Equilibration temperatures for amphiboles were calculated using the amphibole geothermobarometer of Ridolfi et al (2010). Results show temperature values that range from 940-1010°C for basaltic andesites, 900-1080°C for basaltic rocks, 930-1000°C for IAB-type gabbros and 720-800°C for OIB-type gabbros.…”
Section: P-t-f O 2 Conditions Of Magma Chambermentioning
confidence: 99%
See 1 more Smart Citation
“…Equilibration temperatures for amphiboles were calculated using the amphibole geothermobarometer of Ridolfi et al (2010). Results show temperature values that range from 940-1010°C for basaltic andesites, 900-1080°C for basaltic rocks, 930-1000°C for IAB-type gabbros and 720-800°C for OIB-type gabbros.…”
Section: P-t-f O 2 Conditions Of Magma Chambermentioning
confidence: 99%
“…Results show temperature values that range from 940-1010°C for basaltic andesites, 900-1080°C for basaltic rocks, 930-1000°C for IAB-type gabbros and 720-800°C for OIB-type gabbros. Ridolfi et al (2010) reported uncertainties of ±22°C for the amphibole geothermometer. These temperature estimates are generally lower than the crystallization temperature of a normal basaltic magma (>1200°C) (Lee et al, 2009).…”
Section: P-t-f O 2 Conditions Of Magma Chambermentioning
confidence: 99%
“…Empirical and experimental studies indicate that the composition of amphiboles can record the crystallization conditions (P, T, fO 2 , fH 2 O) of magmas (e.g., Johnson and Rutherford, 1989;Ernst and Liu, 1998;Alonso-Perez et al, 2009;Ridolfi et al, 2010;Krawczynski et al, 2012). The studied cumulates contain abundant amphibole crystals suggesting that amphiboles most likely records the temperature and pressure (depth) of the cumulate formation and perhaps one of the main differentiation level in the Ditrău Alkaline Massif.…”
Section: Crystallization Conditionsmentioning
confidence: 93%
“…Using the empirical thermobarometric formulations of Ridolfi et al (2010), amphibole phenocryst core compositions within the Huequi lavas have been used to estimate pressure, temperature, oxygen fugacity and melt water content at the time of amphibole crystallisation (Fig. 6).…”
Section: Hornblende Compositionsmentioning
confidence: 99%
“…6. Thermobarometric relationships for Huequi amphibole compositions, calculated using the method of Ridolfi et al (2010). Black lines show stability limits of typical calc-alkaline compositions (cf.…”
Section: Geochemistrymentioning
confidence: 99%